Development of an Integrated Low-Cost GPS/Rate Gyro System for Attitude Determination - Wang, Chaochao; Lachapelle, Gérard; Elizabeth Cannon, M. (Journal of navigation, 2004)
The use of low-cost GPS receivers and antennas for attitude determination can significantly reduce the overall hardware system cost. Compared to the use of high performance GPS receivers, the carrier phase measurements from low-cost equipment are subject to additional carrier phase measurement errors, such as multipath, antenna phase centre variation and noise. These error sources, together with more frequent cycle slip occurrences, severely deteriorate attitude determination availability, reliability and accuracy performance. This paper presents the investigation of a low-cost GPS/gyro integration system for attitude determination. By employing the dead reckoning sensor type, the ambiguity search region can be specifically defined as a small cube to enhance the ambiguity resolution process. A Kalman filter is implemented to fuse the rate gyro data with GPS carrier phase measurements. The quality control system based on innovation sequences is used to identify cycle slip occurrences and incorrect inter-antenna vector solutions. The availability of the integrated system also improves with respect to the GPS standalone system since the attitude parameters can be estimated using the angular rate measurements from rate gyros during GPS outages. The low-cost hardware used to design and test the integrated system consists of CMC Allstar receivers with the OEM AT575-70 antennas and Murata ENV-05D-52 piezoelectric vibrating rate gyroscopes. Tests in the urban area demonstrated that the introduction of rate gyros in a GPS-based attitude determination system not only effectively decreased the noise level in the estimated attitude parameters but coasted the attitude output during GPS outages and also significantly improved the system reliability.